The complete chloroplast genome sequence of Erigeron breviscapus and Erigeron multiradiatus (Asteraceae). Issue 2 (3rd July 2019) - Li, Zhong-Ji; Liu, Ying-Ying; Yang, Cong-Wei; Qian, Zi-Gang; Li, Guo-Dong
Abstract: The complete chloroplast genomes of Erigeron breviscapus (Vant.) Hand-Mazz and Erigeron multiradiatus (Lindl.) Benth were reported in this study. The complete chloroplast genomes were 152, 367 bp and 152, 281 bp for E. breviscapus and E. multiradiatus, respectively. Erigeron breviscapus including two inverted repeat (IRs, 24, 692 bp) regions, one large singe copy region (LSC) and one small singe copy region (SSC) of 84, 881 bp and 18, 102 bp, whereas E. multiradiatus contained IRs of 24, 691 bp, LSC of 84, 789 bp and SSC of 18, 110 bp. The chloroplast genomes both contained 129 genes, including 84 protein-coding genes, 37 tRNA genes, and 8 rRNA genes.